2019
DOI: 10.1016/j.ijmedinf.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to accept health information and communication technologies: A population-based survey of community-dwelling older adults

Abstract: Introduction: The development of health information and communication technologies (HICTs) could modify the quality and cost of healthcare services delivered to an aging population. However, the acceptance of HICTs-a prerequisite for users to benefit from them-remains a challenge. This population-based study aimed to 1) explore the acceptance of HICTs by community-dwelling older adults as well as the factors associated to the overall acceptance/refusal of HICTs; 2) identify the factors associated with confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Second, they had anxiety about their families relying too much on ICT services and consequently, reducing contact or visits. Prior researches have also pointed out that using ICT services may potentially replace human interactions and make older adults feel lonelier (Abolhassani et al, 2019). In this context, studies have also found that older adults feel isolation anxiety (Kirmizioglu et al, 2009), loneliness (Holmén & Furukawa, 2002), and boredom (Bantwal, 2016) in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Second, they had anxiety about their families relying too much on ICT services and consequently, reducing contact or visits. Prior researches have also pointed out that using ICT services may potentially replace human interactions and make older adults feel lonelier (Abolhassani et al, 2019). In this context, studies have also found that older adults feel isolation anxiety (Kirmizioglu et al, 2009), loneliness (Holmén & Furukawa, 2002), and boredom (Bantwal, 2016) in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of Health Information National Trends Survey 5 (HINTS 5)-Cycle 3 data in 2003-2005 indicated that only 10% of adult internet users communicated with the clinicians through web-based communication services [ 9 ]. Age can be a potential factor affecting the use of e-communication [ 13 , 14 ]. Clarke et al’s [ 14 ] study showed that young adults preferred text messaging, middle-aged adults preferred phone calls, and older adults preferred paper-based and in-person interactions with clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…As the use of technology can facilitate an independent life in old age, users of technology need to possess adequate knowledge and skills (i.e., technological literacy (TL)) [ 1 ], encompassing the ability to interact with and understand technical products [ 2 ]. Older persons are increasingly using mobile technologies as communication tools, such as technology-based health communication (HC), which has been shown to assist in finding information [ 3 , 4 , 5 , 6 ]. Research on mobile assistive technologies used by older persons with cognitive impairment (CI) has found that tablets and smartphones may benefit such users but should be adapted to their needs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%